If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + -10whenq = 13 Reorder the terms: -10ehnqw + q = 13 Solving -10ehnqw + q = 13 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1q' to each side of the equation. -10ehnqw + q + -1q = 13 + -1q Combine like terms: q + -1q = 0 -10ehnqw + 0 = 13 + -1q -10ehnqw = 13 + -1q Divide each side by '-10hnqw'. e = -1.3h-1n-1q-1w-1 + 0.1h-1n-1w-1 Simplifying e = -1.3h-1n-1q-1w-1 + 0.1h-1n-1w-1
| 2y^2-y=28 | | 10y=2x-15 | | 161/14 | | -8a-5=163 | | 14/161 | | x2-2=-7x/4 | | tan(2x)=tan(x+30) | | 3+12=-5(9x-3) | | 3(x+12)+8x=11x-36 | | (3+x)(2x-5)=(x+3)x | | fx-gx=x | | -8z+z=5z+8+5z | | m+-3n=7 | | 6+8=5x | | 41+13x=36 | | X+11=7x+35 | | 27x=24x+6 | | -7-5(6-m)=-43+5m | | 5x^2+3-23=0 | | x+61=80+x+55 | | 2x+4x=(5-3y) | | Z=(2-3j)+(5-4j^3) | | 8(n+4)=10(n-10)-2n | | 5x+4=10x | | 2x+4x(5-3y)= | | 30x-5y=40 | | 3(w+2)-5w= | | 9x+6-3x=6+5x+9 | | .5x+.333x+63=30 | | -3(x-6)=-4+5 | | 9(y-3)=7+8y | | z^2-(3-2i)z+(5-i)=0 |